2014
DOI: 10.4236/jep.2014.514134
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Arsenic Level in Tube-Wells in Bam Province (Burkina Faso)

Abstract: Groundwater is a main source of water supply for populations in Burkina Faso where there is a serious problem for drinking water access. However, water quality has not been always followed regularly. Recent studies showed that more than 50% of drillings in Yatenga province (north of Burkina Faso) have an arsenic concentration above the recommended WHO requirement. Preliminaries studies conducted in Bam (Center North of Burkina Faso) showed high arsenic level in certain localities. This work presents for the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
3
1
Order By: Relevance
“…The weights of mango fruit components ( (1988) for Amélie, Brooks, Keitt and Springfield varieties. On the other hand, these values were higher than those measured in the same varieties coming from the same locality (Banfora) (Somé et al, 2014).…”
Section: Physicochemical Characteristicscontrasting
confidence: 74%
See 2 more Smart Citations
“…The weights of mango fruit components ( (1988) for Amélie, Brooks, Keitt and Springfield varieties. On the other hand, these values were higher than those measured in the same varieties coming from the same locality (Banfora) (Somé et al, 2014).…”
Section: Physicochemical Characteristicscontrasting
confidence: 74%
“…were not significantly different (p<0.05). Other studies performed in Burkina Faso found that Amélie had the highest β-carotene content among the six mango varieties (Somé et al, 2014). In Chinese mango varieties, β-carotene contents ranged from 2.57 to 6.14 mg/100 g pulp (Liu et al, 2013).…”
Section: Colors Of the Pulpsmentioning
confidence: 79%
See 1 more Smart Citation
“…Molybdenum blue can also be used for the detection of arsenate. The reduction of arsenomolybdate produces the colour change and can be noticed at 870 nm wavelength (Some et al 2014). A positive association between Arsenic level in drinking water and hair samples of female respondents has also been studied (Abbas and Cheema, 2014).…”
Section: Introductionmentioning
confidence: 99%